Analyses of Short Stories Using Lacanâ€™s Psychoanalysis - Muhammad Arief Budiman; Ikha Listyarini (Universitas Dian Nuswantoro, 2018)
Abstract. Short stories tell story about imaginative people called characters, including the ones in the monthly magazines and online sources. The purpose of this research is to know the characteristics of the characters portrayed in the short stories published in monthly magazine â€œNurul Hayatâ€ and online sources. This research is qualitative descriptive. The subject of research is 15 short stories; 12 short stories from monthly magazine â€œNurul Hayatâ€ and three short stories from websites. Data collection tools use documentation. Data analysis techniques are using Miles and Huberman techniques. The results indicate that the short stories published in â€œNurul Hayatâ€ magazines and in the website deliver positive and constructing ideas. Those stories tell that as a person we should not easily give up when facing difficult obstacles. They also say that all obstacles can be overcome as Lord does not create them exceeding the human capability. It means that when we try our best, there will be solutions to the problems we face. For that, the researchers agree if these kinds of stories will be used as teaching media to the children.Keywords: lacanian psychoanalyses, short storiesÂ Abstrak. Cerita pendek (cerpen) mengisahkan tentang orang khayalan yang disebut karakter, termasuk cerpen-cerpen dalam majalah bulanan dan online. Tujuan penelitian ini adalah untuk mengetahui karakteristik tokoh-tokoh yang digambarkan di dalam cerita pendek yang terbit dalam majalah bulanan â€œNurul Hayatâ€ dan sumber online lainnya. Penelitian iniÂ merupakan penelitian deskriptif kualitatif. Subjek penelitian ini adalah 15 cerita pendek; 12 cerita pendek dari majalah bulanan â€œNurul Hayatâ€Â dan tiga cerita pendek dari sumber online. Metode pengumpulan data menggunakan metode dokumentasi. Teknik analisis data menggunakan teknikÂ Miles and Huberman. Hasil dari peneltiian ini mengindikasikan bahwa cerpen-cerpen yang terbit dalam majalah bulanan â€œNurul Hayatâ€ dan sumber online memberikan ajaran positif dan membangun. cerpen-cerpen itu mengajarkan bahwa kita tidak boleh menyerah dengan mudah ketika kita menghadapi berbagai macam masalah. cerpen-cerpen tersebut juga mengisahkan bahwa semua masalah dapat diatasi seperti pepatah yang mengatakan bahwa Tuhan tidak memberikan cobaan melebihi kemampuan manusia. ini berarti bahwa ketika kita mencoba yang terbaik, maka akan ada solusi untuk masalah yang kita hadapi. untuk itu peneliti setuju jika cerpen digunakan sebagai media bahan ajar.Kata kunci: psikoanalisis Lacan, cerita pendek